Supervision and Evaluation of Inclusive Education - Nuphanudin Nuphanudin; Aan Komariah; Dedy Achmad Kurniady; Camelia Rizki Hana; Nilam Sukma Pawening; Tasya Nabilah; Puteri Azzahrah Madjid (STAI Hubbulwathan Duri, 2021)
This research aims to monitor and evaluate inclusive education and consider strategies that the government can implement. Is it library research thinking was obtained from seven different international research article websites. Article search was prioritized for publications with a timeframe between 2013 and 2021. We got 13 qualitative reviews. The obstacles faced are the common knowledge of educators, inadequate infrastructure, minimal accessibility, and limited learning resources. The strategy carried out is the need for commitment from the authorities to supervise and evaluate inclusive education, which is supported by continuous support from the government during the implementation process in the field. The government's commitment to allocate funding resources and collaboration with other stakeholders is believed to realize education for all.